2016
DOI: 10.3311/ppci.8194
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Refractory Brick Wastes (RBW) as a Supplementary Cementitious Material in a Concrete

Abstract: The main purpose of this study is to evaluate the reuse of refractory brick wastes (RWB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
4
11
0
Order By: Relevance
“…According to Figure 1, the substitution of 10% of the cement by the pozzolan has a beneficial effect on the mechanical performance and displays a clear improvement in the mechanical resistances compared to the control concrete (UHPFC00). This is explained by the fact that the introduction of pozzolana acts on the hydration reactions by pozzolanic reactions of welldispersed cement grains with portlandite ((Ca(OH)2), thus modifying their speed of growth and morphology [11][12][13][14][15].…”
Section: Effect Of Pozzolan On the Mechanical Performance Of Uhpfcmentioning
confidence: 99%
“…According to Figure 1, the substitution of 10% of the cement by the pozzolan has a beneficial effect on the mechanical performance and displays a clear improvement in the mechanical resistances compared to the control concrete (UHPFC00). This is explained by the fact that the introduction of pozzolana acts on the hydration reactions by pozzolanic reactions of welldispersed cement grains with portlandite ((Ca(OH)2), thus modifying their speed of growth and morphology [11][12][13][14][15].…”
Section: Effect Of Pozzolan On the Mechanical Performance Of Uhpfcmentioning
confidence: 99%
“…According to Table 4, dune sand has a beneficial effect on mechanical performance and shows a significant improvement in the bending and compressive strength of the concretes studied compared to the UHPC0 control concrete. This is because the addition of finely ground dune sand affects the hydration reactions by pozzolanic reaction of well-dispersed cement grains with portlandite ((Ca (OH)2), thus modifying their growth rate and morphology [16][17][18][19][20].…”
Section: Effect Of Dune Sand On the Mechanical Performance Of Uhpcsmentioning
confidence: 99%
“…For example, one study proposed the use of refractory brick waste as supplementary material in cement for use in concrete. In addition, the use of three types of refractory waste substitutes for silica fume was highlighted, and the performance of refractory-added cement in concrete was found to be satisfactory [25]. Another study demonstrated the use of refractory waste in concrete mortars as an aggregate material to replace one of the aggregates normally used [26].…”
Section: Introductionmentioning
confidence: 99%